2021
DOI: 10.1038/s41598-021-86280-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of laser speckle flowgraphy pulse waveform parameters for the evaluation of the optic nerve head and retinal circulation

Abstract: To characterize laser speckle flowgraphy (LSFG) pulse waveform parameters for ocular circulation evaluation, a multicenter, prospective, cross-sectional study was conducted in 111 eyes of 86 healthy Japanese individuals. Optic nerve head (ONH) tissue-area, vessel-area mean blur rate (MT and MV, respectively), and MT and MV pulse waveform parameters were obtained using LSFG and ONH structural parameters using planimetry. Multivariate linear mixed-effects modeled regression analysis identified factors contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 63 publications
2
9
1
4
Order By: Relevance
“…Disc area was also associated with MBR-T in both sexes and in the group overall (overall, β = -0.16, p = 0.003; male, β = -0.21, p = 0.021; female, β = -0.15, p = 0.028). This finding is compatible with a previous study conducted with healthy subjects [25]. Although IOP was associated with MBR-T in the overall…”
Section: Plos Onesupporting
confidence: 93%
See 2 more Smart Citations
“…Disc area was also associated with MBR-T in both sexes and in the group overall (overall, β = -0.16, p = 0.003; male, β = -0.21, p = 0.021; female, β = -0.15, p = 0.028). This finding is compatible with a previous study conducted with healthy subjects [25]. Although IOP was associated with MBR-T in the overall…”
Section: Plos Onesupporting
confidence: 93%
“…As already mentioned, it has been suggested that MBR-T is a good indicator of structural and functional changes in glaucoma [13,33]. FAI-T is an indicator of the instantaneous force that can increase OBF in a short time [25]. A case-control study of patients with European ancestry has shown that NTG patients have lower FAI-T (i.e., a flattened pulse waveform) than healthy subjects [52].…”
Section: Pulse Waveform In the Onh And Antioxidant Capacity In Glaucomamentioning
confidence: 96%
See 1 more Smart Citation
“…In this study we investigated the change of blood ow to the MV and MT. The MV re ects blood ow in the major retinal vessels supplied by the central retinal artery and vein, while the MT re ects blood ow in the ONH peripheral circulation supplied by the short posterior ciliary artery and vein [20]. We found that both MT and MV were decreased, compared to past reports of normal subject data with similar average age [21,22].…”
Section: Discussioncontrasting
confidence: 52%
“…The LSFG disk area, as measured in pixels, showed moderate to strong correlation with the disk area, as measured on magnification-corrected pictures taken by fundus camera in healthy Japanese subjects. 26 …”
Section: Methodsmentioning
confidence: 99%